Actively compensation of low order aberrations by refractive shaping system for high power slab lasers. (December 2015) - Xue, Zheng-wei; Guo, Ya-ding; Chen, Zhong-zheng; Li, Shuai; Xu, Yi-ting; Xu, Jian; Wang, Bao-shan; Gong, Ke-ling; Gao, Hong-wei; Bo, Yong; Peng, Qin-jun; Cui, Da-fu; et al.
Abstract: We present a compact refractive shaping system for actively compensating low order aberrations of high power slab lasers. The shaping system includes three spherical lenses and two cylindrical lenses. Both theoretical and experimental investigations were performed to evaluate the compensation capability of the refractive shaping system. For a typical input beam with large low order aberrations of peak-to-valley (PV)=66.10 λ and root-mean-square (RMS)=16.05 λ, adjusting the distance between lenses, the wavefront aberrations are reduced to PV=0.48 λ, RMS=0.10 λ for the theoretical simulation and PV=0.50 λ, RMS=0.11 λ for the experimental result, respectively. It indicates that the main low order aberrations of defocus and 0° astigmatism can be significantly compensated by actively adjusting the distance between lenses and the experimental result agree well with the theoretical simulation. Highlights: The low order aberration compensation method based on refractive shaping system. Low order aberrations of high power slab lasers can be actively compensated. Large magnitude low order aberrations can be well compensated by this method. Large magnitude aberrations and stroke limit of deformable mirrors can be bridpged.